Intergenerational Differences in Health Information-Sharing Behavior: An Experimental Study on the Mediation of PAD Emotional Structure and the Moderation of Risk Framework (The Journal of Medicine, Humanity and Media, 2024)
Family is the basic unit of society and is usually where the communication of health information starts. Thus, intergenerational communication and persuasion of about health information has been an important topic in the field of health communication. This study examines intergenerational differences in health communication and explores the causes of these differences from the perspective of the structure of feeling. An interaction experiment shows that generational differences, as a single physical connection, may not be the only cause of the audience's emotional structure; rather, a dual social connection consisting of both intergenerational differences and the information framework may be the primary cause. The emotions of pleasure and dominance play intermediary roles between generational difference and users’ behavior of sharing health information. However, the degree of arousal is not an efficient intermediary. By understanding the cognitive path of microbehaviors and providing empirical evidence, this study hopes to reduce "inefficient public information" in intergenerational health communication and to facilitate more precise communication.
Keywords: Health Communication; Generational Difference; PAD Model; Risk Framework